Structural basis of damage recognition by thymine DNA glycosylase: Key roles for N-terminal residues. Issue 21 (31st August 2016) - Coey, Christopher T.; Malik, Shuja S.; Pidugu, Lakshmi S.; Varney, Kristen M.; Pozharski, Edwin; Drohat, Alexander C.
Abstract: Thymine DNA Glycosylase (TDG) is a base excision repair enzyme functioning in DNA repair and epigenetic regulation. TDG removes thymine from mutagenic G·T mispairs arising from deamination of 5-methylcytosine (mC), and it processes other deamination-derived lesions including uracil (U). Essential for DNA demethylation, TDG excises 5-formylcytosine and 5-carboxylcytosine, derivatives of mC generated by Tet (ten-eleven translocation) enzymes. Here, we report structural and functional studies of TDG 82-308, a new construct containing 29 more N-terminal residues than TDG 111-308, the construct used for previous structures of DNA-bound TDG. Crystal structures and NMR experiments demonstrate that most of these N-terminal residues are disordered, for substrate- or product-bound TDG 82-308 . Nevertheless, G·T substrate affinity and glycosylase activity of TDG 82-308 greatly exceeds that of TDG 111-308 and is equivalent to full-length TDG. We report the first high-resolution structures of TDG in an enzyme-substrate complex, for G·U bound to TDG 82-308 (1.54 Å) and TDG 111-308 (1.71 Å), revealing new enzyme-substrate contacts, direct and water-mediated. We also report a structure of the TDG 82-308 product complex (1.70 Å). TDG 82-308 forms unique enzyme–DNA interactions, supporting its value for structure-function studies. The results advance understanding of how TDG recognizes and removes modified bases from DNA, particularly those resulting from deamination.